Preparation, Characterization and Phenol Adsorption of Mangifera kemanga Blume Seed - Siti Hadiati Mardiah; Dian Arrisujaya; Devy Susanty; Nia Yuliani (JURNAL SAINS NATURAL, 2022)
The potential of Mangifera kemanga Blume., an inexpensive biosorbent, for removing of hazardous substances such as phenols from its aqueous solution has been studied. The authors used Scanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR) Spectrometers, and quantification to study the morphology and characterization of Mangifera kemanga Blume. seeds (MKS) biomass, as well as batch experiments to determine the percentage of phenol removed when pH, contact period, biosorbent dosage, and phenol concentration were varied. The Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich isotherm models had been used to interpret the experimental results. The optimal values found in our research correspond to a pH of 6 for an MKS dosage of 35 g/L and a contact time of 45 minutes for initial phenol concentrations ranging from 5 to 25 mg/L.  The result indicated that MKS was a particularly successful adsorbent for phenol chemisorption from aqueous solution.Keywords: adsorption;  endemic; Bogor; Mangifera kemanga; phenol